CFD Analysis into the Resistance of Trimaran with Longitudinal Sidehull Adjustments - Luhulima, Richard Benny; Sutiyo, Sutiyo; Utama, I Ketut Aria Pria (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2021)
There has recently been a surge in demand for multi-hull vessels for military and commercial purposes. The need for multi-hull ships increase from the necessity to balance speed and cargo requirements. Among others, the trimaran is one such hull type. The current study performs a CFD resistance analysis for trimaran as a parameter range of feasible hull forms based on the NPL systematic series. The resistance of trimaran hull shapes are calculated using CFXTM, a commercial CFD code that belongs to ANSYS. The trimaran model was tested at one fixed transverse separation (S/L=0.2) together with 3 longitudinal separations, R/L=0, 0.25, and 0.5, at different Froude numbers (based on length) from 0.2 to 0.6. Testing on the individual hull is also carried out to quantify the effect of resistance interference on the trimaran configuration. The CFD simulation results indicate that the trimaran model with side hulls parallel to the stern (R/L=0) has the least resistance. The interference effect of resistance on Trimaran with R/L=0, 0.25, 0.5 are 2.8%, 4.6%, 6.8% as opposed to non-interference trimaran model, respectively. These findings provide an approach for appropriately selecting the trimaran model with longitudinal side hull configurations.